Pemanfaatan Modifikasi Permainan Trivial Pursuit Sebagai Media Pembelajaran Guna Meningkatkan Kosakata Bahasa Inggris Anak - Riska Nasella (EduBasic Journal: Jurnal Pendidikan Dasar, 2019)
The mastery and use of English is very important for social community, especially for children. Children are potential assets in building the nation. Their abilities and intelligence should be optimized to create a developed and competitive nation. Seeing that there is still a lack of elementary shool students  in mastering English vocabulary, the researcher were willing to modify the Trivial Pursuit game as learning media to improve children English vocabulary mastery. The Trivial Pursuit game was chosen because this game is very fun when and can unwittingly internalize their knowledge and language. This research was carried out in the historical tourism area of the Banten Lama Kaibon Palace with 10 research subjects and representatives of community elements. This research is qualitative focus on action research where containing the process of planning, making provisions, acting, collecting data, analyzing data, evaluating data, and reflection. The result is proven that there is an improvement in mastery of English vocabulaty after learning by using Trivial Pursuit. The tourisme community also assumed that the action is really helpful to children around tourism site to learn English.